Three dimensional cloud and dynamical structure of Southern Hemisphere extra- tropical cyclones in observations and in a model - Govekar, Pallavi Devidas (2017)
This study, for the first time, investigates the three-dimensional cloud and dynamical structure of extratropical cyclones over the Southern Ocean using both observations and model simulations. The three-dimensional structure of clouds associated with Southern Hemisphere extratropical cyclones is constructed using active observations from the CLOUDSAT and CALIPSO satellites. First, a composite cyclone is constructed from cyclones in 400S - 500S in the years 2007 and 2008 using the cyclone center as the composite reference point. It is shown that the three-dimensional cloud distribution around a composite cyclone captures well-known features of conceptual models of extratropical cyclones with thick high top clouds in the frontal region and low clouds of varying depth behind the system. Composite mean fields of sea level pressure, vertical motion, potential temperature and relative humidity are superposed on the three dimensional cloud structure to identify key links of the cyclone dynamical structure with the cloud field. Further, the relationship between dynamical and cloud processes in full three dimensions around cyclones is quantified. The change in relationship between clouds and dynamical fields with cyclone strength and life cycle are investigated. The ACCESS (Australian Community Climate and Earth System Simulator) model is compared to CloudSat/ CALIPSO observations. Model fields for MSLP, omega, relative humidity and cloud fraction are examined. The model cyclones were tracked using the MSLP field of the model. The overall cloud structure is qualitatively reproduced by the model. However, high-level cloud occurrence is overestimated while low-level cloud occurrence is severely underestimated. There are too few clouds behind the system and too many high clouds in the warm frontal region, compared to observations. It is found that the range of most dynamical variables in the composite cyclone is smaller than observed, indicating that the dynamical properties of the model cyclones are not well simulated. ...